2022
DOI: 10.3390/curroncol29070391
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related LncRNAs to Construct a Prognosis Risk-Assessment Model for Gastric Cancer

Abstract: Background: Gastric cancer is a prevalent cause of tumor death. Tumor immunotherapy aims to reshape the specific immunity to tumors in order to kill the tumor. LncRNAs play a pivotal role in regulating the tumor immune microenvironment. Herein, immune-related lncRNAs were used to establish a prognosis risk-assessment model for gastric cancer and provide personalized predictions while providing insights and targets for gastric cancer treatment to enhance patient prognosis. Methods: Gastric adenocarcinoma transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With the gradual application of tumor immunotherapy in clinical practice, researchers are actively exploring tumor immunotherapy for GC, which is expected to bring hope to GC patients. 36 Tumor immunotherapy aims to reshape the specific immunity against tumors in order to kill them. LncRNAs play a pivotal role in regulating the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…With the gradual application of tumor immunotherapy in clinical practice, researchers are actively exploring tumor immunotherapy for GC, which is expected to bring hope to GC patients. 36 Tumor immunotherapy aims to reshape the specific immunity against tumors in order to kill them. LncRNAs play a pivotal role in regulating the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…We explored differentially expressed genes in high- and low-risk groups using the R package (limma) with |log 2 FC| ≥ 1 and FDR < 0.05 as filters [ 24 ]. Then, the enrichment of differential genes was explored using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) with a filter condition of p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, a risk score model was built based on multivariate Cox regression analyses that showed the altered status of the DNAm-driven gene signature was significantly associated with the overall survival (OS) of patients with GC. Shilin Zhi et al (2022) [14] screened the immune-related lncRNAs from TCGA database and identified 13 lncRNAs to construct a prognosis assessment model that assigned the patients to different risk groups and was expected to provide a novel target for immunotherapy in patients with GC. Zepang Sun et al (2020) [80] revealed a novel prognostic factor by a multivariate analysis, a genomics score (GS) comprising 7 miRNAs, 8 mRNA, and 19 DNA methylation sites, which provides additional precision in stratifying patients with different OS prognoses.…”
Section: Omics Data (Excluding Radiomics)mentioning
confidence: 99%